Evolution and origin of Blue Stragglers in 47 Tucanae. Issue Volume 14:Issue S351(2019) (May 2019) - Parada, Javiera; Richer, Harvey; Heyl, Jeremy; Kalirai, Jason; Goldsbury, Ryan
Abstract: Using data from the core of 47 Tuc we have identified stars in different evolutionary stages in the colour-magnitude diagram, and used the effects of mass segregation on their radial distribution to study the evolution and origin of blue stragglers (BSS). We separate the BSS into 2 samples by their magnitude and find considerable differences in their distribution. Bright BSS are more centrally concentrated with mass estimates over twice the turn-off mass suggesting an origin involving a triple or multiple star system. The distribution of the faint BSS is close to that of the main-sequence (MS) binaries pointing to these stars as their likely progenitors. Using MESA models, we calculate the expected number of stars in each evolutionary stage and compare it with the observed number of stars. Results indicate that BSS have a post-MS evolution comparable to that of a normal star of the same mass and a MS-BSS lifetime of about 200 – 300 Myr.